PHYSIOLOGICAL AND SANITARY QUALITY OF DESICCATED AND STORED AZUKI BEAN SEEDS - Tavares, Cássio Jardim (2016)
The objective of this research was to evaluate the effects of using different herbicides as desiccants in pre-harvest and the effects of storage on the physiological and sanitary quality of azuki bean seeds (Vigna angularis Willd). The experiment was arranged in a randomized complete block design in a split plot scheme, with four replications. Four herbicides were tested: paraquat (400 g a.i. ha-1), glufosinate ammonium (400 g a.i.  ha-1), glyphosate (720 g a.i. ha-1), flumioxazin (30 g a.i. ha-1) and a control without herbicide application. In the subplots seed quality was tested in two evaluation periods: at harvest and six months after harvest. Desiccant was applied when the azuki beans were physiologically mature. We assessed the physiological and sanitary quality of the seeds using a vigour and seed health test. The use of glyphosate resulted in a higher incidence of abnormal seedlings and reduced size and weight of the seedlings. With paraquat and flumioxazin the physiological quality was maintained and there was reduced pathogen infestation in the seeds six months after harvest. Storage affected the physiological quality of the azuki bean seeds.